Show me a sign - LeZotte, Ann Clare; Morstad, Julie (2020)
Mary Lambert has always felt safe and protected on her beloved island of Martha's Vineyard. Her great-great-grandfather was an early English settler and the first deaf islander. Now, in 1805, over a hundred years later, many people there -- including Mary -- are deaf, and nearly everyone can communicate in sign language. Mary has never felt isolated. She is proud of her lineage. But recent events have delivered winds of change. Mary's brother died, leaving her family shattered. Tensions over land disputes are mounting between English settlers and the Wampanoag people. And a cunning young scientist has arrived, hoping to discover the origin of the island's prevalent deafness. His maniacal drive to find answers soon renders Mary a "live specimen" in a cruel experiment. (Written by a deaf author and based upon a true story.)
Ages 8-12.
Grades 4-6.
Keywords: Deaf children -- Juvenile fiction; Kidnapping victims -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Human experimentation in medicine -- Juvenile fiction; Wampanoag Indians -- Juvenile fiction; Sign language -- Juvenile fiction; Chilmark (Mass.) -- History -- 19th century -- Juvenile fiction; Martha's Vineyard (Mass.) -- History -- 19th century -- Juvenile fiction; Fiction; Historical fiction; History; Juvenile works; Psychological fiction; Historical fiction; Psychological fiction